Penerapan Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SDN Cipinaha Kecamatan Gunung Tanjung - Zakiyah, Suci; Ai Siti Sulastri (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2024)
Learning outcomes are the end of the completion of the learning process in the world of education. To get good learning results teachers must play an important role in using interesting and varied learning models. This research aims to find out how much the fifth grade science learning outcomes of SDN Cipinaha, Gunung Tanjung District have improved through the application of the Guided Inquiry learning model. This research was carried out in May 2024. The sample in this research was 15 students of class V at SDN Cipinaha in the 2023/2024 academic year. The research method used in this research is a quantitative method with sampling, namely saturated sampling. Learning outcome data was taken from the results of the pre-test and post-test with 10 questions. To analyze the data, researchers used SPSS version 25 software. Based on non-parametric t-test calculations, the significance value (2-tailed) was 0.001 < 0.05, indicating that there was a difference. which is significant between the initial variable (Pre Test) and the final variable (Post Test). This shows that there is a significant influence on the differences in treatment given to each variable.